HUMAN DHX9 HELICASE UNWINDS TRIPLE HELICAL DNA STRUCTURES - Jain, Aklank (2010)
Naturally occurring poly(purine·pyrimidine) rich regions in the human genome are prone to adopt non-canonical DNA structures such as intramolecular triplexes (i.e. H-DNA). Such structure-forming sequences are abundant and can regulate the expression of several diseases-linked genes. In addition, the use of triplex-forming oligonucleotides (TFOs) to modulate gene structure and function has potential as an approach to targeted gene therapy. Previously, we found that endogenous H-DNA structures can induce DNA double-strand breaks and promote genomic rearrangements. Herein, we find that the DHX9 helicase co-immunoprecipitates with triplex DNA structures in mammalian cells, suggesting a role in the maintenance of genome stability. We tested this postulate by assessing the helicase activity of purified human DHX9 on various duplex and triplex DNA substrates in vitro. DHX9 displaced the third strand from a specific triplex DNA structure and catalyzed the unwinding with a 3′→5′ polarity with respect to the displaced third strand. Helicase activity required a 3′-single-stranded overhang on the third strand and was dependent on ATP hydrolysis. The reaction kinetics consisted of a pre-steady-state burst phase followed by a linear, steady-state pseudo-zero-order-reaction. In contrast, very little, if any helicase activity was detected on blunt triplexes, triplexes with 5′-overhangs, blunt duplexes, duplexes with overhangs, or forked duplex substrates. Thus, triplex structures containing a 3′-overhang represent preferred substrates for DHX9, where it removes the strand with Hoogsteen hydrogen-bonded bases. Our results suggest the involvement of DHX9 in maintaining genome integrity by unwinding mutagenic triplex DNA structures.